Insurgency, terrorism, and counterterrorism in Africa - Kieh, George Klay; Kalu, Kelechi A. (Lexington Books, 2023)
Insurgency, Terrorism, and Counterterrorism in Africa, edited by George Klay Kieh, Jr. and Kelechi A. Kalu, addresses the need for a systematic understanding and examination of insurgent movements and terrorist organizations, as well as state policies that instigate intrastate conflicts in African states. It examines and documents the tactics that are used by anti-government forces, states' counterterrorism responses, and the human security impacts of insecurity on citizens across various communities in Africa. The contributors' extensive research methods include case studies that explore activities of terrorist organizations like Al Shabaab, Al Qaeda, Boko Haram, and the Islamic State. It presents new and productive insights about counterterrorism strategies deployed by selected African states, the African Union, and the U.S. A historically rich and politically focused analysis of states as co-conspirators in terrorism-induced insecurity in Africa, this book challenges existing literature on terrorism that largely focuses on the actions of non-state entities. It provides practical insights to policymakers that desire to end insecurity and promote inclusive governance in Africa.